The International Criminal Court and Africa : one decade on / edited by Evelyn A. Ankumah. - Ankumah, Evelyn A.; Ferencz, Benjamin B., 1920- (Africa Legal Aid series ;, 2016)
More than ten years ago the International Criminal Court (ICC) was established as a universal court meant to achieve criminal justice worldwide. That goal still stands, but so far the Court has dedicated most of its time and resources to African conflicts in which international crimes have been committed. While the ICC can be said to contribute to criminal justice in Africa, it cannot be denied that the relationship between the Court and the continent has been troublesome. The ICC has been accused of targeting Africa, and many African states do not seem willing to cooperate with the Court. Debates on Africa and international criminal justice are increasingly politicised. The authors of this volume all recognise the current problems and criticism. Yet they do not side with populist pessimists who, after just over a decade of ICC experiences, conclude that the Court and international criminal justice are doomed to fail. Rather, the contributors may be regarded as cautious optimists who believe there is a future for international criminal justice, including the ICC. The contributors use their unique specific knowledge, expertise and experiences as the basis for reflections on the current problems and possible paths for improvement, both when it comes to the ICC as such, and its specific relationship with Africa.